Symmetric Dopant‐Free Si Solar Cells Enabled by TiOx Nanolayers: An In‐Depth Study on Bipolar Carrier Selectivity - Takuya Matsui; Shohei Fukaya; Shona McNab; James McQueen; Kazuhiro Gotoh; Hitoshi Sai; Noritaka Usami; Ruy Sebastian Bonilla (Advanced Science, 2025)
Abstract High‐efficiency solar cells require two contact structures, engineered for efficient extraction of photogenerated holes and electrons at the respective electrodes. Herein, crystalline Si solar cell featuring hole‐ and electron‐selective passivating contacts composed entirely of a single material, amorphous titanium oxide (TiOx), without extrinsic doping is demonstrated. The hole/electron selectivity of the TiOx layers (≈5 nm) is tailored by the oxidation process and the choice of Ti precursor in the atomic layer deposition (ALD). Ex situ and in situ X‐ray photoelectron spectroscopy measurements elucidate that the hole‐selective TiOx induces significant band bending in the Si (Φ≈0.7 eV), generating a p‐type inversion layer in the n‐Si absorber. The electron‐selective TiOx induces a smaller band bending of Φ<0.35 eV. This clarifies that the bipolar carrier selectivity of TiOx is associated with the different amount of negative fixed charges generated during the ALD process, depending on the choice of Ti precursor and oxidant. In addition, the growth of a hydrogen‐containing SiOy nanolayer (≈1‐1.5 nm) at the Si/TiOx interface during postdeposition oxidation is crucial for providing chemical passivation in both types of TiOx. These findings pave the way for a deeper understanding of the charge generation mechanism and chemistry at the Si/metal oxide interfaces.